Using the Cre/loxP recombination system to study the role of the PI3K/AKT signalling transduction pathway and the embryonic cellular origin of adult haematopoietic stem cells in the zebrafish - Jalali, Maryam (2013)
Haematopoietic stem cells (HSCs) are present in the bone marrow (BM) and maintain our blood system throughout life. These cells have clinical importance and their transplantation constitutes the most common type of stem cell therapy available. Lack of BM donors and our inability to expand HSCs ex vivo; make it desirable to be able to generate patient specific HSCs from pluripotent stem cells. Using the zebrafish as model organism we have two parallel long-term projects, one to address the cellular origin of HSCs and the other to understand an aspect of the molecular programming of HSCs. Establishing a CreERT2 system we have labelled cells by inducing with 4-OHT at different time points during embryonic development. Since lineage tracing experiment are long term experiments, only a part of this was done. During this project, however methods to isolate, section and stain the adult zebrafish kidney, which is the site of adult haematopoiesis in the fish, have been established which would later be used to look at the kidneys of the fish that have been recombined in order to trace the origin of the cells that seed the kidney.